Winter's no time to sleep! - Green, Poppy; Bell, Jennifer (Jennifer A.), 1977- (New York : Little Simon, 2015)
While Sophie Mouse and her forest friends are playing in the snow one day, they accidentally wake a hibernating hedgehog named Pippa, who is a little grumpy at first, but Sophie, Hattie, and Owen show her all the fun things to do in wintertime.
Keywords: Mice -- Juvenile fiction; Forest animals -- Juvenile fiction; Winter -- Juvenile fiction